2020
DOI: 10.1002/ijfe.2063
|View full text |Cite
|
Sign up to set email alerts
|

Does financial inclusion enhance economic growth? Empirical evidence from the IsDB member countries

Abstract: This innovative study examines the effect of financial inclusion measured by financial inclusion index (FII) on the economic growth of the Islamic Development Bank (IsDB) member countries. The data were collected on different elements of financial inclusion and economic growth for the period 2000-2016.To draw multi-dimensional results, we have set up the panel data for 45 countries, and we estimated the generalized method of moments (GMM), two-stage least squares (2SLS), panel vector autoregressive (VAR) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…The Hansen and Sargan test was applied to examine the instrument’s reliability and control the over-identifying restrictions in the analysis. Therefore Hansen test and Sargan tests to estimate the other restrictions were also validated [ 24 , 70 ]. The number of instruments (J-statistics) employed is 51, which indicates that the two-step system GMM is a valid instrument for this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hansen and Sargan test was applied to examine the instrument’s reliability and control the over-identifying restrictions in the analysis. Therefore Hansen test and Sargan tests to estimate the other restrictions were also validated [ 24 , 70 ]. The number of instruments (J-statistics) employed is 51, which indicates that the two-step system GMM is a valid instrument for this study.…”
Section: Resultsmentioning
confidence: 99%
“…Generalized methods of moments (GMM) provide better results with correct model specifications than single-equation models and techniques. Two-step system GMM is the best suitable, where we do not know the distribution of the dependent variable [ 70 ]. The lag-value of SD is taken in GMM to make it a dynamic model and avoid the issue of autocorrelation as prevails in the static regression model.…”
Section: Methodsmentioning
confidence: 99%
“…High purchasing power indicates higher money transactions so that these transactions can be made easier by mobile banking. Those who work will feel comfortable when financial transactions can be done anywhere and anytime (Ali et al, 2021;Kang et al, 2012;Souiden et al, 2021). It also helps them, even more, when they are at work to use mobile banking to still make financial transactions while working.…”
Section: Occupation and Mobile Bankingmentioning
confidence: 99%
“…This closeness becomes a hope for banks and also, of course, the government because people who are increasingly open to banking products show progress in a country (Chiu et al, 2017;Merhi et al, 2020). A high level of financial inclusion can increase economic growth because banking transactions can help increase people's purchasing power and increase money circulation within a country (Ali et al, 2021;Lal, 2021;Nandi et al, 2021). In addition, the ease of transactions that is upheld by mobile banking can increase the opportunities for the internationalization of business actors in a country (Gregori, 2021;Mataveli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…is is because in addition to the different definitions of financial inclusion, past studies have mostly focused on the linear effect or overall effect between financial inclusion and economic growth, ignoring the potential nonlinear effect or regional heterogeneity between them. As pointed out by Ali et al [67], when exploring the economic impact of financial inclusion, it is necessary to include nonlinear effects or cross-group factors in the study, which can indicate the optimal strategy in different situations. When Li et al [13] analyzed the economic growth effect of financial inclusion, they found that there was a significant positive impact in eastern China, but no significant impact in the central and western regions.…”
Section: E Interactive Relationship Between Financial Inclusion and E...mentioning
confidence: 99%